Pengaruh Influencer Marketing, Brand Image, Product Design, Product Quality Terhadap Purchase Intention Di Masa Pandemi Covid-19 (Studi Kasus pada Brand Erigo di Kota Malang) - Anindita Salasa Ahmada; Rois Arifin; Andi Normala (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to examine the influence of Influencer Marketing, Brand Image, Product Design, Product Quality on Purchase Intention during the Covid-19 Pandemic (Case Study on Brand Erigo in Malang City). This type of research is explanatory research using a quantitative approach. The sampling technique used in this study is non-probability sampling with a purposive sampling approach. The data collection method in this study was carried out by distributing online questionnaires with a Likert scale given to respondents who intend to buy products from the Erigo brand. The sample used in this study were 90 respondents. Research data were analyzed using IBM SPSS software. The results of this study found that the variables of influencer marketing, brand image, product design, product quality have a simultaneous effect on purchase intention. The results of this study also found that the influencer marketing variable had no effect of 0.540 on purchase intention. The brand image variable was found to have an effect of 0.019 on purchase intention. The product design variable was found to have an effect of 0.005 on purchase intention. The product quality variable was found to have no effect of 0.054 on purchase intention. Based on the results of this analysis, the Erigo brand should use influencer marketing with a positive and strong appeal and select prospective influencer marketing who have credibility that can represent the product. Second, the Erigo brand is expected to improve the quality of Erigo products in terms of materials. Third, the Erigo brand is expected to always try to maintain and improve the company's brand image for its products and is expected to continue to innovate in product design so as to increase the purchasing value of consumers to buy Erigo products, because design is one of the important tools to face the rapid market competition in the business world. Keyword: influencer marketing, brand image, product design, product quality, purchase intention.